Ca2+ loading within mitochondria affects arrhythmogenesis in rat right ventricular hypertrophy. (25th November 2020) - Sato, H; Someya, Y; Nishiyama, M; Kumasaka, K; Satoh, W; Shindoh, C; Miura, M
Abstract: Introduction: Delayed afterdepolarizations (DADs) causes triggered arrhythmias, and intracellular Ca2+ (Cai) waves play important roles in the formation of DADs. It remains unclear, however, whether Ca2+ loading within mitochondria affects arrhythmogenesis in right ventricular (RV) hypertrophy. Purpose: We focused on the properties of Cai wave propagation, investigating whether changes in Ca2+ loading within mitochondria affects arrhythmogenesis in a rat model of RV hypertrophy. Methods: Rats were given a subcutaneous injection of 60 mg/kg monocrotaline (MCT-rats) or solvent (Ctr-rats). Four weeks after the injection, trabeculae were dissected from RVs. Force was measured using a silicon strain gauge, membrane potential using a microelectrode, Cai using microinjected fura-2 and a CCD camera, and ROS production using 2', 7'-dichlorofluorescein (DCF) fluorescence. Cai waves and arrhythmias were induced by electrical stimulation (24°C). To change Ca2+ loading within mitochondria, Ru360 (10 μM), a mitochondrial calcium uptake inhibitor, was added. Results: MCT-rats showed lower survival rate (p=0.075), higher RV systolic pressure (48.8±4.6 vs 21.3±6.5 mmHg), and heavier weight ratio of RV free wall to left ventricle (LV) (0.44±0.03 vs 0.25±0.04). MCT-rats showed a wider action potential (APD90, 320±20 vs 205±11 ms), a higher diastolic Cai (177±20 vs 110±8 nM), and faster and larger Cai waves (p<0.01). The velocity and amplitude of Cai waves were correlated with the diastolic Cai in Ctr- and MCT-rats. The velocity of Cai waves in MCT-rats was higher than that in Ctr-rats at the given amplitude of Ca2+ waves (p<0.01). The velocity and amplitude of Cai waves was linearly correlated with the amplitude of DADs in Ctr- and MCT-rats. Ru360 decreased the inducibility of arrhythmias in some trabeculae (MCT-A-rats, n=7), while it did not change it or it inversely increased it in the others (MCT-B-rats, n=11). RV systolic pressure in MCT-A-rats was higher than that in MCT-B-rats (62.2±6.0 vs 41.0±5.2 mmHg), and the weight ratio of RV to LV in MCT-A-rats was higher than that in MCT-B-rats (0.51±0.04 vs 0.41±0.03). The changes in Cai wave propagation velocity after the addition of Ru360 was inversely correlated with the weight ratio of RV to LV (r=−0.64) and the RV pressure (r=−0.60, n=7), suggesting that under the condition of severe RV hypertrophy due to higher RV pressure, reduction of Ca2+ within mitochondria results in a decrease in the velocity of the Cai waves, thereby improving of arrhythmias. In the presence of Ru360, DCF oxidation rate was decreased during 0.5 or 2.5 Hz electrical stimulation (n=5, p<0.05). Conclusions: In RV hypertrophy, acceleration of Cai waves occurs due to an increase in diastolic Cai and an increase in Ca2+ sensitivity of the SR Ca2+ release channels, thereby causing arrhythmias. In more severe RV hypertrophy, Ca2+ within mitochondria may also be involved in arrhythmogenesis probably through an increase in ROS production. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid for Scientific Research (C) from Japan Society for the Promotion of Science